Review review of methods for texture analysis of myocardium from echocardiographic images: a means of tissue characterization. - Kerut EK; Given M; Giles TD (Echocardiography, 2003)
This review discusses the definition of texture and identifies its utility in echocardiography for characterization of tissue. Methods used for quantification of texture in echocardiography and other disciplines are discussed. Several methodologies, particularly the wavelet method of texture quantification, seem to be promising. Image texture analysis appears to be a fertile area for research in echocardiography. (ECHOCARDIOGRAPHY, Volume 20, November 2003)